Formulation of Gel from Corn Silk Extract (Stigma maydis) and Burns Healing Activity - Noni Rahayu Putri; Nessa Nessa; Yoga Ramadhana (Faculty of Medicine, University of Jember, 2021)
Corn silk (Stigma maydis) contains compounds that play a role in wound healing, such as flavonoids, saponins, tannins. This study aims to formulate a gel from corn hair extract and see its activity in healing burns. The test group was divided into four groups: group I (hot metal induction), group II (without extract ), group III (corn hair extract concentration 5%), and group IV (comparison B®), which metal induction. The parameters observed were % wound healing, epithelialization time, and histopathology. The results of the study on the average% of burns healing rate 7, 14 and 21 days, namely group I (27,92%; 62,42%; 100%), group II (35,39%; 60,16%; 100%), group III (44,05%; 63,69%; 100%) and group IV (32,81%; 66,48%; 100%). The mean time of tissue peeling epithelialization groups I, II, and III was on day 16, and group IV was on day 17. For the histopathological results, the mean score of collagen fibers, fibroblast cells, and epithelialization was respectively group I (2,2; 2,7; 2), group II (2,8; 2,9; 2), group III (3,3; 2,9; 2,7), and Group IV (3,9; 3; 3). The results of the two-way ANOVA statistical test on % burn healing (p> 0.05) and one-way ANOVA at the time of epithelialization (p> 0.05) and the histopathological score (p <0.05) showed that group III (the corn hair extract 5 %) could influence the process of healing burns. Keywords: Burns, Corn Silk Extract (Stigma maydis), % Burn Healing, Epithelialization Time, Histopathology